A Fuzzy Logic Approach for Remote Healthcare Monitoring by Learning and Recognizing Human Activities of Daily Living - Medjahed, Hamid; Istrate, Dan; Boudy, Jérôme; Baldinger, Jean Louis; Bougueroua, Lamine; Dhouib, Mohamed Achraf; Dorizzi, Bernadette (IntechOpen, 2012)
None